TOXICITY TESTING OF SOURSOP LEAF EXTRACT (Annona muricata l.) AS AN ANTICANCER CANDIDATE WITH THE BRINE SHRIMP LETHALITY TEST (BSLT) METHOD - Wauran, Vania Patrisia (PHARMACON, 2024)
Soursop leaves (Annona muricata L.) contain several secondary metabolite compounds including alkaloids, flavonoids, tannins, saponins, steroids and is one of the plants used to prevent and treat cancer. This study was conducted with the aim of knowing whether the secondary metabolite compounds contained in soursop leaves and the potential of soursop leaves as anticancer candidates against Artemia salina Leach larvae. The extraction method used to extract soursop leaves is the maceration method using 96% ethanol solvent. Phytochemical screening tests in this study include examination tests for alkaloids, flavonoids, tannins, saponins, steroids and triterpenoids. Toxicity testing using the Brine Shrimp Lethality Test (BSLT) method using 4 concentrations (1000 ppm,  100 ppm, 10 ppm, 1 ppm) and carried out three replication. The results of research obtained in phytochemical screening tests, soursop leaves have alkaloid, flavonoids, tannins, saponins, and compound. The results showed that the total death toxicity testing at a concentration of 1000 ppm 83%, at a concentration of 100 ppm 67%, at a concentration of 10 ppm 47% and at a concentration of 1 ppm 30%. The higher the concentration of soursop leaf extract, the higher the mortality from shrimp larvae and the LC50 value of  12.57 ppm. Based on  the LC50 value , it can be concluded that soursop leaf extract has the potential as an anticancer candidate and is very toxic because had an LC50 which < 30 ppm.